Impact of Downsizing on Employees due to the Economic Crisis - Jain, Pranav (2011)
The research study covered the effects of downsizing during the economic crisis at Tata Motors, India on victims and survivors. A total of 20 participants were selected, who as a result of downsizing and corporate restructuring, went through a lot of difficulties. As organizations downsize, employees must be ready to accept changes in their personal and professional lives. The participants in this study were employees of a Fortune 500 automotive company in Asia. To analyse the impact of downsizing on the participants, semi-structured interviews were used for data collection. The research questions had adhered to every level within the organization; from the upper management to the lower management. NVIVO 9 software was used to gather the data. The study exposed that the positive outcome was that the employees are adjusting to the changes that have taken place in the organization as a result of downsizing and they remain hopeful for future job prospects. But there were negative impacts as well like marital issues, mental stress and future job prospects. The survivors had experienced role transition and its effects are analysed. In addition, the research aimed to determine if these participants fit in with the Mishra-Spreitzer model (1998). The survivors experienced different emotions as compared to the victims. They had negative effects like lack of trust in leadership and lack of communication from the top management. They initially had negative emotions regarding their new job but this eventually faded away with time onto positive emotions. A positive outcome expected from this research is that there would be a better understanding of the effects of downsizing that can help both organizations and employees.